Balancing form, function and aesthetic: A study of ruling patterns for zodiac men in astro-medical manuscripts of late Medieval England - Witherden, SCV (Pace University Press, 2017)
The Zodiac Man is an image of a man marked with astrological signs according to the parts of the body over which those signs were thought to have influence. In the late medieval period, when such diagrams commonly appeared in astro-medical texts, efficient access to this information would have been especially useful for physicians attempting to determine the best time for bloodletting. However, Zodiac Men diagrams often betray a desire to be visually impressive as well as practical, whilst having to negotiate with the manuscript form too. The ruling patterns for Zodiac Men, i.e. the lines organising text and image on the page, provide a crucial insight into these interlocking imperatives. This article provides a survey of different approaches to ruling Zodiac Men in late medieval English astro-medical manuscripts—especially the Kalendarium of John Somer—before examining the functional, aesthetic, and social implications of these choices.